Being young, black, woman academics on an Accelerated Development Programme in an Historically White University in South Africa: a narrative analysis - Mohoto, Nkoe Lieketso Paballo (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2017)
The national program for the development of next and new generation academic professionals (NGAP) aims to help Universities to diversify their academic teaching staff to be more reflective of the national demographics of the country. Through NGAP and policies of redress, a Historically White University would predictably introduce young black women into their academic teaching staff. This is a category of the population who would have been most affected by the exclusionary hiring policies that would have generally been in use in historically white universities before 1995, the year following the first democratic elections. The selection of staff according to criteria that has historically been used to exclude them is a policy which is widely considered to be a useful and necessary way to institute redress. While this half thesis does not disagree with this social and moral imperative, I find interest in the lack of focus on the emotional, psychological, spiritual and otherwise personal toll of the implementation of such a policy on those who are introduced through it and related policies. I believe there is a need to problematise the highly normative environments in which staff (to benefit from redress) are required to function. This half thesis examines the narrated experiences of three such staff members at Rhodes University with specific interest in their everyday experiences in an institution which has historically been tailored for (and in many cases is still run by) white, older male academics. The thesis indicates that the emotional and psychological effects and 'taxes' of being on an accelerated development programme may be worth noting and appreciating in order to think about the retention of black woman academics. The findings show that the complexity of younger black women's experiences within historically white universities such as Rhodes University requires equally complex and multifaceted strategies and programmes. These programmes should not only support these academics but also undermine existing exclusionary institutional cultures in order to facilitate true, deep transformational practice in historically white universities such as Rhodes University.
Keywords: New generation academic professionals Programme (South Africa); College teachers, Black -- South Africa; Women college teachers, Black -- South Africa -- Case studies; Rhodes University